Minimally invasive lateral transiliac sacroiliac joint fusion using 3D-printed triangular titanium implants - Patel, Vikas (Med Devices (Auckl), 2019)
Background: Minimally invasive sacroiliac joint (SIJ) fusion (SIJF) has become an increasingly accepted surgical option for chronic SI joint dysfunction, a prevalent cause of chronic low back/buttock pain. Objective: To report clinical and functional outcomes of SIJF using 3D-printed triangular titanium implants (TTI) for patients with chronic SI joint dysfunction. Methods: A total of 28 subjects with SIJ dysfunction at 8 centers underwent SIJF with 3D TTI and had scheduled follow-up to 6 months (NCT03122899). Results: Mean preoperative SIJ pain score was 79.1 and mean preoperative Oswestry Disability Index (ODI) was 49.9. At 6 months, pain scores decreased by 51 points and ODI decreased by 23.6 points (both p<0.0001). The proportion of subjects able to perform various back/pelvis-related physical functions with minimal difficulty improved significantly for nearly all activities. Opioid use decreased and physical function, as assessed with three objective tests, improved. Conclusion: Early results from this prospective multicenter trial confirm that clinical responses to a 3D triangular titanium implant for SIJF are similar to those from prior trials, with improved physical function and decreased opioid use. Level of evidence: Level II.